The Relationship Between Urine Test Findings and Disease Outcomes in Hospitalized Patients With COVID-19 - Nafiseh Amerion; Hossein Ebrahimi; Shahrbanou Goli; Hossein Bagheri; Marzieh Rouhani (نشریه پرستاری ایران)
Background & Aims COVID-19 can cause serious kidney issues. To diagnose kidney function and diseases of the urinary tract, a complete urine test is needed. This study aims to determine the relationship between complete urine test findings and disease outcomes in patients with COVID-19 admitted to a hospital in Shahroud, Iran. Materials & Methods This is a descriptive-analytical study with a cross-sectional design. In this study, 1134 data related to the patients with COVID-19 admitted to Imam Hossein Hospital affiliated to Shahroud University of Medical Sciences from March 20, 2020 to June 20, 2021 were examined. The diagnosis of COVID-19 was based on a positive nasal or nasopharyngeal swabs by RT-PCR test, or the result of a lung CT scan showing ground-glass opacities. Three checklists were used to record demographic data, urine test findings, and disease outcomes. Logistic regression analysis and independent and dependent t-tests were used for data analysis. Results Urine appearance, bacteria in urine, blood in urine, castes in urine, crystals in urine, protein in urine, red blood cells in urine, white blood cells in urine, yeast cells in urine, colony count in urine, and positive urine culture had a significant relationship with death and their hospitalization in ICU (P<0.05). Also, ketone in urine, mucus in urine, and specific gravity of urine had a significant relationship with the intubation in ICU (P<0.05). Conclusion The changes in urine test parameters in patients with COVID-19 is associated with the disease outcomes. Therefore, accurate monitoring of urinary parameters in these patients is recommended for rapid diagnosis of any complications related to the disease.